2009
DOI: 10.1080/02705060.2009.9664266
|View full text |Cite
|
Sign up to set email alerts
|

Shelter Occupancy by Mixed-Species Pairs of Native Signal Crayfish and Non-Native Red Swamp Crayfish Held in Enclosures

Abstract: Sheltering ability does not appear to confer an advantage to non-native red swamp crayfish (Procambarus clarkil) in a small, western Washington lake where the invader outnumbers the native signal crayfish (Pacifastacus leniusculus). When paired with similar-sized non-native P. clarkii, P. leniusculus was adept a t monopolizing limited artificial shelter inside enclosures placed on the bottom of Pine Lake. In these contests, the dominant crayfish or winner was typically the one with longer chelae, or, in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…and P. leniusculus (Mueller and Bodensteiner, 2009). Coexistence at a small scale was in fact observed in this study, with non-tagged crayfish of both species often being visually detected in the same area.…”
Section: Discussionmentioning
confidence: 94%
“…and P. leniusculus (Mueller and Bodensteiner, 2009). Coexistence at a small scale was in fact observed in this study, with non-tagged crayfish of both species often being visually detected in the same area.…”
Section: Discussionmentioning
confidence: 94%
“…A few studies have begun to investigate the ecology and potential impacts of P. clarkii in the Pacific Northwest. Mueller and Bodensteiner (2009) did not find competitive dominance of P. clarkii over native P. leniusculus under field conditions in a Washington lake. Olden et al (2009b) observed that P. clarkii was less predatory on an invasive snail common to Washington than P. leniusculus.…”
Section: Red Swamp Crawfish (Procambarus Clarkii)mentioning
confidence: 61%
“…Researchers in the southeastern United States (US) are increasing efforts to document and conserve the region's endemic crayfish diversity (e.g., Welsh et al 2010), while researchers in the Great Lakes region and California have made important contributions quantifying the economic and ecological costs associated with crayfish invasions (e.g., Gamradt and Kats 1996;Keller et al 2008). By contrast, few recent studies on distributions, ecology, or management of crayfish have been conducted in the Pacific Northwest region of the US and Canada (but see Lewis 1997;Bondar et al 2005a;Mueller and Bodensteiner 2009). This oversight is somewhat surprising given the unfortunate history of crayfish invasions and conservation in adjacent California, where the native sooty crayfish (Pacifastacus nigrescens) was declared extinct in 1977, and the native Shasta crayfish (Pacifastacus fortis) is listed under the US Endangered Species Act.…”
Section: Introductionmentioning
confidence: 96%